The aim of this research was to analyze mercury reduction power from patient urine with teeth amalgam which used for mercury detoxification. The research was descriptive which isolate 5 samples of patient urine from Bahu PUSKESMAS. Bacteria were grow in a - Fatimawali, Fatimawali (UNIVERSITAS SAM RATULANGI, 2013)
The objective of this research was to determine the species or genus of mercury resistant bacteria culture from mercury polluted waters. Microbiology identification of culture S3.2.2 was done with morphology, physiology and biochemistry test. Molecular analysis was done by amplifying 16S rRNA gene using PCR method. Universal Bact- F1 forward/Uni-B1 Reverse was using as primer. Amplification result was electrophorize with agarose 1,5%, furthermore sequencing was done against 16SrRNA gene. The result shows that culture S3.2.2 were negative grams bacteria, rod shaped, nonmotil, catalase (+), citrat (+), H2S (-), fermentase (+), indol (+) and lisin (+). Blast analysis against nucleotide sequence of 16S rRNA gene possesses 99% similarities with Klebsiella pneumoniae.